The impact of cell-of-origin, MYC/Bcl-2 dual expression and MYC rearrangement on disease relapse among early stage diffuse large B-cell lymphoma patients treated with combined modality therapy. Issue 6 (12th May 2021) - Augustyn, Alexander; Medeiros, L. Jeffrey; Ludmir, Ethan B.; Gunther, Jillian; Fang, Penny; Li, Shaoying; Ok, Chi Young; Bankston, Mikaela E.; Verma, Vivek; Pasalic, Dario; Ahmed, Sairah; Nastoupil, Loretta J.; et al.
Abstract: We addressed the prognostic impact of cell-of-origin (COO), MYC and Bcl-2 overexpression as well as isolated MYC rearrangement among 111 patients with limited stage diffuse large B-cell lymphoma (DLBCL) treated with consolidative radiation therapy (RT) after a metabolic complete response to immunochemotherapy. With a median follow-up of 31.1 months (95% CI 27.4 − 34.8), 4 relapses occurred. The 3-year progression free survival (PFS), overall survival (OS), and loco-regional relapse free survival (LRFS) for the cohort were 95%, 96%, and 100%, respectively. There were no differences in OS, PFS, or LRFS based on COO or MYC/Bcl-2 dual expression (DE). Similarly, patients with MYC translocations without BCL2 or BCL6 rearrangements did not have worse outcomes. Consolidative RT produced excellent local control, regardless of DLBCL biology, with one late in-field failure.